Pengembangan Media Promosi Melalui Tiktok Menurut Perspektif Ulama - muhammad rudi hartanto (AL-ITTIFAQ: Jurnal Ekonomi Syariah, 2022)
Social media is a gathering place for information from various parts of the world. Social media has experienced an increase in its users, especially the Tiktok application, which has been downloaded 1.46 billion times in 2022. Tiktok itself is a social media for sharing short videos in a vertical format. Tiktok social media nowadays has become a strategic place in marketing a product or brand that consumers can easily reach. Promotion using social media tiktok is a step from a seller so that his product is known and consumers are interested in buying it. Which adjusts to today by looking at the various and varied promotions now. This study aims to look at the various views of scholars on the development of promotional media through the social media Tiktok. know the development of Tiktok application-based promotional media to increase buying interest. and can find out the feasibility of promotional media based on the tiktok application. the research method used is a qualitative descriptive method with data collection used includes interviews, observation, documentation.